The impact of emotional intelligence towards employees’ performance / Nur Raihan Mohamad - Mohamad, Nur Raihan (Faculty of Business and Management, 2019)
The purpose of this study was to analyse the impact of emotional intelligence (EI) on employees’ performance in Bank Rakyat Twin Tower, Bangsar. The factor that affect employees’ performance are Self-Awareness, Self-Management and Social Awareness. Furthermore, this research was guided by two research objectives which the research needs to answer. The research is quantitative research which the research used self-administered questionnaires as instrument to collect data. The data had been collected from 80 respondent by using convenience sampling method. The data are coded using Statistical Package for Social Science (SPSS) version 22.0 after collecting information from the respondents. The study recommended that Bank Rakyat Twin Tower, Bangsar need to focus on self-management because because it gives the biggest impact towards employees’ performance. As well as the organization need to focus on self-management and self-awareness as it can lead to the positive behaviors toward work environment which then achieve organizational goals and objectives.